Delayed Macular Hole Closure - Peter Distelmaier (Case Reports in Ophthalmology, 2014)
Purpose: The presented case raises questions regarding the favorable scheduling of planned postoperative care and the ideal observation interval to decide for reoperations in macular hole surgery. Furthermore a discussion about the use of short- and long-acting gas tamponades in macular hole surgery is encouraged. Methods: We present an interventional case report and a short review of the pertinent literature. Results: We report a case of spontaneous delayed macular hole closure after vitreoretinal surgery had been performed initially without the expected success. A 73-year-old male Caucasian patient presented at our clinic with a stage 2 macular hole in his left eye. He underwent 23-gauge pars plana vitrectomy and internal limiting membrane peeling with a 20% C2F6-gas tamponade. Sixteen days after the procedure, an OCT scan revealed a persistent stage 2 macular hole, and the patient was scheduled for reoperation. Surprisingly, at the date of planned surgery, which was another 11 days later, the macular hole had resolved spontaneously without any further intervention. Conclusions: So far no common opinion exists regarding the use of short- or long-acting gas in macular hole surgery. Our case of delayed macular hole closure after complete resorption of the gas tamponade raises questions about the need and duration of strict prone positioning after surgery. Furthermore short-acting gas might be as efficient as long-acting gas. We suggest to wait with a second intervention at least 4 weeks after the initial surgery, since a delayed macular hole closure is possible.